Experimental Evaluation of Vertebral Strain in Lumbar Total Disc Replacement - Semitela, A. (2020)
Background mainly in the United States, because the insurance companies have refused to reimburse surgeons for fear of delayed complications, revisions and unknown secondary costs. Typical long-term vertebrae-implant related structural complications include subsidence, migration, implant displacement, endplate fracture, wear and loosening. Intervertebral disc implant size, shape, position, endplate removal and compressive strength of trabecular bone further affect the risk of implant subsidence and loosening. The aim of the present study is to understand the combined effects of the different depth positioning of the ProDisc-L implant and endplate removal during surgery on the vertebral bone strain behaviour. Manufactured synthetic spinal L3-L4 segments were used to experimentally predict vertebrae cortex strain behaviour for different depth implant positioning and endplate thickness removal. In addition, validated finite element models were developed to assess the structural behaviour of cancellous-bone. Measured cortex strains showed significant differences relative to the intact vertebra for the most extreme depth implant positioning. The endplate thickness reduction tends to decrease significantly compressive cortex strains for all strain gauges. A two- to three-fold cancellous-bone strain increase occurs when more than 50% of the endplate thickness is removed, independently of the depth implant position. It is concluded that the implanted strain distribution that better fits intact vertebra strain behaviour is achieved when the depth centred implant position is combined with a partial endplate thickness removal.